Retrovirus-Derived RTL/SIRH: Their Diverse Roles in the Current Eutherian Developmental System and Contribution to Eutherian Evolution - Tomoko Kaneko-Ishino; Fumitoshi Ishino (Biomolecules, 2023)
Eutherians have 11 retrotransposon Gag-like (RTL)/sushi-ichi retrotransposon homolog (SIRH) genes presumably derived from a certain retrovirus. Accumulating evidence indicates that the RTL/SIRH genes play a variety of roles in the current mammalian developmental system, such as in the placenta, brain, and innate immune system, in a eutherian-specific manner. It has been shown that the functional role of Paternally Expressed 10 (PEG10) in placental formation is unique to the therian mammals, as are the eutherian-specific roles of PEG10 and PEG11/RTL1 in maintaining the fetal capillary network and the endocrine regulation of RTL7/SIRH7 (aka Leucine Zipper Down-Regulated in Cancer 1 (LDOCK1)) in the placenta. In the brain, PEG11/RTL1 is expressed in the corticospinal tract and hippocampal commissure, mammalian-specific structures, and in the corpus callosum, a eutherian-specific structure. Unexpectedly, at least three RTL/SIRH genes, RTL5/SIRH8, RTL6/SIRH3, and RTL9/SIRH10, play important roles in combating a variety of pathogens, namely viruses, bacteria, and fungi, respectively, suggesting that the innate immunity system of the brain in eutherians has been enhanced by the emergence of these new components. In this review, we will summarize the function of 10 out of the 11 RTL/SIRH genes and discuss their roles in eutherian development and evolution.